Cabecar serratus, a new genus and species of leptohyphid mayfly from Central America, and description of the imaginal stages of Tricorythodes sordidus Allen (Ephemeroptera: Leptohyphidae) - Baumgardner, David E.; A., Socorro Ávila (Zootaxa, 2006)
Cabecar serratus, gen. n., sp. n., is described based upon larvae and reared adults from the costal regions of Costa Rica, Nicaragua, and Panamá. The imago stage of Tricorythodes sordidus Allen is also described for the first time from reared larvae from Nicaragua and Costa Rica.